Thromboprophylaxis after hospital discharge in acutely ill medical patients: need for trials in patients who are at high risk of venous thrombosis - Nemeth, Banne; Lijfering, Willem M.; Cannegieter, Suzanne C. (Journal of Thoracic Disease, 2017)
Venous thrombosis (VT), composing deep vein thrombosis (DVT) and pulmonary embolism (PE), is a commonly occurring complication following hospitalization. Patients hospitalized for acute medical illnesses, such as heart failure, respiratory failure, a flare of inflammatory bowel disease or acute neurologic disease have an eightfold risk for the development of VT as opposed to the general population (1). For this reason, guidelines advise to prescribe in-hospital thromboprophylaxis to reduce the rate of symptomatic VT in acutely ill medical patients (2). Randomized, controlled trials of anticoagulants vs. placebo in such hospitalized medical patients have shown a reduction of more than 50% in the rate of VT, that outweighed the small absolute increase in major bleeding (3). For this reason guidelines recommend the use of low-dose anticoagulants among patients at high risk for thromboembolism for 6 to 14 days but advise against extended-duration thromboprophylaxis after hospital discharge (2,4). However, the duration of this thromboprophylaxis is disputed because of several reasons. First, physicians have to weigh the benefits of prolonged treatment against the risks such as major and clinical relevant non-major bleeds introduced by anticoagulant therapy (5). Second, literature shows that, the risk of VT remains markedly increased for at least the first month after hospital discharge (6). And third, the heterogeneity of hospitalized medical patients makes it difficult to translate results derived from earlier trials (that studied the efficacy of extended thromboprophylaxis therapy) to individual patients (7). For instance, extended duration low-molecular weight heparin has seemed to prevent VT more than it increased major bleeding events only in patients with immobility, the elderly or women (5).